Penguatan Peran Penyimbang Adat dalam Pelayanan bagi Kesejahteraan Masyarakat Adat Buwai Khunjung di Pekon Maja, Kecamatan Kalianda, Lampung Selatan - Damar Wibisono; Suwarno Suwarno; Pairul Syah; Yuni Ratna Sari; Dewi Ayu Hidayati; Ifaty Fadliliana Sari; Erna Rochana (Nengah Nyappur, 2026)
This community service activity aims to strengthen the role of the Penyimbang Adat (traditional leaders) in delivering services for the welfare of the Buwai Khunjung Indigenous Community at the Central Secretariat of Pekon Maja, Kalianda Subdistrict, South Lampung. The Saibatin traditional governance structure in this area still faces problems, including the limited understanding of some Penyimbang Adat regarding their roles, stagnation in the renewal of the customary institutional structure, and the low effectiveness of the penyimbang's role in promoting the economic welfare of indigenous communities. The activity was carried out through a sociological approach involving preliminary observation and interviews, brainstorming and focus group discussion (FGD), as well as socialization and training delivered through lectures, discussions, and simulations to 15 traditional leaders and community members in Pekon Maja. Evaluation was conducted using pre-test and post-test instruments to measure changes in participants' understanding, complemented by an impact evaluation through questionnaires. The results showed an increase in participants' understanding of customary governance leadership, the functions and roles of traditional government heads, and the role of the penyimbang in services for indigenous community welfare, with the average score increasing from 62.67 in the pre-test to 76.00 in the post-test, or a 13.33% increase. Participants also demonstrated strong enthusiasm through active involvement in discussions and simulations. This activity contributes to strengthening collective understanding of an ideal model of customary governance structure that can be replicated in other Saibatin indigenous communities in Lampung Province, while also providing a foundation for the sustainability of local-wisdom-based customary institutional mentoring programs